Experimental and Numerical Analyses of Eccentric Bolted Connections Subject to Shear and Torsion - Zanaty, Mohannad Mahran (AUC Knowledge Fountain, 2026)
Steel connections are one of the pillars of the steel structures construction industry, and yet, it still to this day holds some ambiguities in our design procedures. Several authors believe that the elastic-based methods constricted connection design into a conservative approach, and accordingly initiated a method called Instantaneous Center, which is a method indicating that the center of rotation is around a fictitious point. The method was investigated analytically by exploring the domain and found the method often present multiple roots, with one of the roots often indicating an unrealistic point of rotation with a marginally high exaggerated capacity of the connection. The other realistic root can provide lower strength than that of the elastic method. The investigation is carried out via experimental and numerical methods in six configurations, cross-checked with each with the hypothesized loads from methods. The experimental scheme consisted of six steel brackets loaded to cause shear and torsion on configurations with M10, M12, and M16 bolts. The six setups translated to six finite element models with the material model of the bolt varying based on two approaches, one calibrated by the single shear test and another by a bi-linear material model plastic model based on J2 stress invariant. It was shown that the experimental testing alongside the numerical models follow a trend, where larger diameter and more bolts display larger ductility in the connection. The numerical model consistently had a higher load capacity than the IC method without hardening and was consistently in correlation with the elastic load model. The use of a more realistic bolt constitutive model shows that the connection behaves with little to no hardening. Experimental results had, more correlation with the elastic load method with a minimum error of 0.23% to 14.68% lower than the error range in IC method 1.95% up to 33.03%. This indicates that the IC method must have a lower bound of connection strength governed by the elastic load limit, and must be bound for bolt size, as lower-sized bolts showed no ductile behavior in the connection. It should also definitely be governed by grade as the grade require different ductility per bolt and the ductility of the bolts would affect the ductility of the entire connection.